Progress in Fundamental Research into Supercritical Adsorption and its Impact on Clean Energy Technology - Li Zhou (Adsorption Science & Technology)
Progress in the fundamental research of supercritical adsorption and its impact to the research of clean energy technology are presented. The monomolecular coverage mechanism and an isotherm model were assigned for supercritical adsorption, on the basis of which it was possible to explain the experimental isotherms of supercritical gases in a satisfactory manner. Clarification of the adsorption mechanism of supercritical gases helped to (a) identify what materials to study in a search for better carriers of gaseous fuels and (b) indicate the best route to take in a search for an improved technology for the separation or purification of this kind of fuel.